Exploration and verification of fourth industrial revolution generic skills attributes for entry-level civil engineers - Fathiyah Mohd Kamaruzaman; Roszilah Hamid; Azrul A. Mutalib; Mohamad Sattar Rasul; Marlissa Omar; Mohd Fakhrul Azizie Mohd Zaid (Institute of Advanced Engineering and Science, 2023)
The fourth industrial revolution (4IR) requires the workforce to be equipped with new skills when existing skills need to be upgraded or improved because they are no longer in line with technological advancement in 4IR. Thus, it is crucial to determine what the new skills or 4IR skills are that can help the future workforce obtain a job after graduation. This study aimed to explore and verify the attributes of nine 4IR generic skills (GS4IR) for entry-level civil engineers in Malaysia by using a qualitative approach. An interview session was conducted with five senior engineers in the civil engineering (CE) field and three experts (two engineers in CE and one lecturer in CE faculty) for reliability data verification. The interview data were analyzed using coding analysis and presented in a matrix table. The results show 76 items identified as attributes of nine GS4IR constructs. Next, the verification of the constructs and attributes of GS4IR was obtained from Fleiss Kappa's reliability analysis to determine the overall approval index. The results of the analysis revealed an overall Kappa coefficient value of 0.61, which indicates a good level of agreement. The findings of this study consist of 58 attributes for nine constructs of GS4IR approved after the inter-rater reliability among the experts. The findings from this study are beneficial for the development of a framework of 4IR generic skills for civil engineering graduates as guidance to instill new skills in producing future engineers.